Adsorbed complex and laboratory geotechnics of Quarry Dust (QD) stabilized lateritic soils - Onyelowe, Kennedy (Environmental Technology & Innovation, 2018)
The effect of ordinary Portland cement, OPC+Quarry Dust, QD on the adsorbed moisture, diffused double layer (DDL), dielectric constant, density and repulsion potential (RP) of treated lateritic soil was investigated through laboratory tests. The preliminary tests showed that the natural soil was an A-2-7 soil, according to the AASHTO classification system, highly plastic soil and high swelling potentials. The soil was treated with a fixed 5% OPC and varying proportions of QD at 5, 10, 15, 20, 25, 30, 35, 40, 45 and 50% by weight of the dry soil. The stabilization results showed that the compaction properties improved consistently, with the addition of the QD. Also, the addition of the QD reduced the adsorbed moisture and consequently reduced the double diffused layer and the repulsion potential, which constitute the properties investigated within the adsorbed complex in the stabilization operation. These observations brought about the cation exchange reaction between the metallic ions that were attracted to the adsorption complex, resulting to densification, flocculation from the natural state of dispersion of particles and strength gain in the stabilization procedure. Results also showed that the repulsion potential increased in magnitude with the distance between the reactive particles and the clay surface and reduced with increased proportions of QD. The dielectric constant also reduced considerably with adsorbed moisture, which indicated that the dielectric was affected by the moisture and the ions released within the adsorbed complex.
Keywords: Adsorbed water; Lateritic soils; Geotechnical engineering; Soil stabilization; Soil–nanostructured ash interaction